Interprofessional training in medical education: competency, collaboration, and multi-level analysis across seven governorates, Egypt - Ehab Kamal; Yousra El-Maradny; Lobna A. Elgamal; Mennatallah Ahmed Alnagdy; Marwa Rashad Salem; Rasha Ashmawy (BMC Medical Education)
Abstract Background Interprofessional Education (IPE) is essential in improving patient outcomes by promoting teamwork and collaboration among healthcare professionals. This study aimed to assess the impact of IPE on developing clinical competencies and collaborative practices in Egyptian intensive care units (ICUs). The core modules focused on managing antibiotic resistance, venous thromboembolism (VTE), and mechanical ventilation (MV), chosen for their high prevalence in Egyptian ICUs and significant impact on patient outcomes. Methods The IPE program was implemented across seven governorates, involving 16 hospitals and multidisciplinary ICU teams. It was conducted in two consecutive four-month waves, each covering the three core modules. Participants included physicians, clinical pharmacists, and ICU nurses. To enhance efficacy, a blended learning approach combined virtual webinars, case-based discussions, and in-person workshops. Data collection included pre- and post-tests, a post-training satisfaction survey, and the Interdisciplinary Education Perception Scale (IEPS) to assess competency improvements. Results The IPE program included 157 participants, with 79 in wave 1 and 78 in wave 2. Physicians were mostly male (47.2%) and older (> 40 years), while clinical pharmacists and ICU nurses were younger and predominantly female (89.6% and 75.7%, respectively). For exam performance, clinical pharmacists had the highest excellence rate (22.4%), while ICU nurses had the highest failure rate (40.5%). Post-training, interprofessional competence improved significantly, with physicians showing the greatest competency gains (p < 0.05) and clinical pharmacists playing a key role in antibiotic resistance management (p = 0.029). Overall satisfaction was high across modules, increasing from 79.8% in Module 1 to 90.5% in Module 3. Higher satisfaction was observed among females (up to 89.5%), participants aged 30–40 (92.6% in Module 2), and those who received sufficient program information (p = 0.011), with lecturers median score rated consistently 5.0, while material satisfaction median score varied (4.0–4.8). Conclusions The IPE program improved interprofessional collaboration and clinical competency, despite challenges such as participant dropout, scheduling conflicts, and engagement in virtual sessions. By addressing issues like antimicrobial resistance and critical care management, it provides a practical model for improving healthcare outcomes, particularly in resource-limited settings. This program is a preliminary step, with plans to expand to more hospitals in Egypt and conduct further research on its long-term impact on patient outcomes and potential for replication in healthcare systems worldwide. Clinical trial number Not applicable.